The business strategies of technological collaboration: Taiwan electronic industry perspective. (20th February 2004) - Lin, Julia; Fang, Shih-Chieh; Hsiao, Luke Y.C.
Taiwanese firms have transformed their strategy from OEM to ODM, which symbolises the improvement of Taiwanese firms' technology to some extent. In addition to developing technology by firms themselves, it is also important to collaborate in various types of technology, if firms desire to maintain their competitiveness and continue to make progress. Thus, researches on the "BSTC" have aroused the attention of scholars both in domestic and foreign countries. At the beginning, this paper will define the concept of technology and BSTC clearly. Second, with the perspective of transaction cost theory and strategic management to integrate the literature of strategy on the technology collaboration, this paper establishes a related theoretical framework to draw the research hypothesis. The data of the Taiwanese electronic industry were examined to ascertain the accuracy of the framework. This paper also concluded the major decisive factors of BSTC. Finally, the conclusions and research implications were presented.